1976
DOI: 10.1111/j.1445-5994.1976.tb03996.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Peripheral Neuropathy: Nerve Conduction Studies Before, During and After Carbamazepine Therapy

Abstract: Fifty-four patients with diabetic peripheral neuropathy were treated with carbamazepine for a period of one year. Clinical assessment and nerve conduction velocity studies (NCV) were done periodically. Forty-nine patients had symptomatic relief of all sensory manifestations but NCV remained essentially unchanged. Untoward effects of the drug were frequent but transitory. It was concluded that carbamazepine is a dependable drug for the treatment of symptomatic diabetic sensory polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, failure of improvement in NCV by pregabalin has been reported by others also [28]. A study conducted in India has also described the similar findings for carbamazepine [29]. On the other hand, a meta-analysis conducted for alpha-lipoic acid has showed significant improvement in NCV [30].…”
Section: Discussionmentioning
confidence: 64%
“…However, failure of improvement in NCV by pregabalin has been reported by others also [28]. A study conducted in India has also described the similar findings for carbamazepine [29]. On the other hand, a meta-analysis conducted for alpha-lipoic acid has showed significant improvement in NCV [30].…”
Section: Discussionmentioning
confidence: 64%
“…The anticonvulsants carbamazepine[134–137], phenytoin[138–140], clonazepam[101] and sodium valproate[63] have been studied in diabetic neuropathic pain. However, only four of these studies have been randomized placebo‐controlled trials[134, 135, 139, 140].…”
Section: Management Of Neuropathic Painmentioning
confidence: 99%
“…Older studies [58][59][60][61] found that carbamazepine was beneficial in one study, although the patients had a variety of neuropathic syndromes [58], two were not RCT [60,61] and the fourth was very brief [59]. The NNT for the positive study [58] was 3.3.…”
Section: Carbamazepinementioning
confidence: 99%